(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The year 2025 presents a complex macroeconomic landscape shaped by evolving monetary policies, geopolitical shifts, and regional economic dynamics. This article explores the major macroeconomic themes expected to influence global and regional economies in 2025, drawing on recent expert analyses and forecasts.